Gender Similarities and Domain-Specific Differences in Religious Motivation among Muslim High School Students in Java - Rian Rokhmad Hidayat; Lilla Maturizka Ayu Asfarina; Laili Daffa Ulima; Hasan Zainnuri; Maylani Cahya Fitriyana (State Islamic University (UIN) Salatiga, 2026)
Religious motivation is an important psychological resource for adolescents, yet limited research has examined gender similarities and differences among Muslim students in general high schools, particularly in the Javanese cultural context. This study aimed to examine overall and domain-specific differences in religious motivation between male and female Muslim high school students in Central and East Java. A quantitative comparative design was used involving 754 students, consisting of 446 female and 308 male respondents selected through convenience sampling. Data were collected using the 14-item Religious Motivation Scale, which showed item validity coefficients ranging from .257 to .559 and good internal consistency, with a Cronbach’s alpha of .869. Descriptive statistics were used to summarize respondents’ characteristics and religious motivation scores, while the Mann–Whitney U test was applied because the normality assumption was not met. The results showed no significant gender difference in overall religious motivation, indicating broad similarity between male and female students. However, small domain-specific differences were found in ubudiah practice and avoidance of unethical practices, with female students showing higher mean ranks in both domains. These findings contribute theoretically by showing that gender differences in religious motivation are culturally situated and domain-specific rather than universal or fixed. Practically, the study supports gender-responsive and non-stereotypical Islamic educational counseling programs. The study is limited by convenience sampling, self-report data, focus on gender, and absence of population-based weighting. Future studies should examine broader contextual factors shaping adolescents’ religious motivation.